Diagn Interv Radiol 2022
DOI: 10.5152/dir.2022.20732
|View full text |Cite
|
Sign up to set email alerts
|

Performance of apparent diffusion coefficient values and ratios for the prediction of prostate cancer aggressiveness across different MRI acquisition settings

Abstract: apparent diffusion coefficient values and ratios for the prediction of prostate cancer aggressiveness across different MRI acquisition settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
2
0
0
Order By: Relevance
“…More specifically, seven out of ten features used by the best model were extracted from the ADC map, including the ADC mean, whose value was demonstrated to have a negative relationship with the probability of high-aggressive PCa ( Figure 6 and Supplementary Section S5 ). This is consistent with the literature since ADC values are demonstrated to be moderately correlated to GG of peripheral zone lesions [ 29 ] and to have a role in differentiating GG2 and PCa with higher grades [ 16 , 30 , 31 , 32 ]. Moreover, it was demonstrated that high-aggressive peripheral zone tumors are associated, on the ADC map, with high values of entropy and low values of energy [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…More specifically, seven out of ten features used by the best model were extracted from the ADC map, including the ADC mean, whose value was demonstrated to have a negative relationship with the probability of high-aggressive PCa ( Figure 6 and Supplementary Section S5 ). This is consistent with the literature since ADC values are demonstrated to be moderately correlated to GG of peripheral zone lesions [ 29 ] and to have a role in differentiating GG2 and PCa with higher grades [ 16 , 30 , 31 , 32 ]. Moreover, it was demonstrated that high-aggressive peripheral zone tumors are associated, on the ADC map, with high values of entropy and low values of energy [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of our study. Similar conclusions about the sensitivity and specificity of ADC in differentiating the risk groups of patients with PCa have been reported in several studies ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 90%